POLA KOMUNIKASI KOMUNITAS DANCE COVER K-POP DALAM MEMBANGUN RASA PERCAYA DIRI ANTAR ANGGOTA (STUDI KASUS KOMUNITAS DANCE COVER K-POP THE KEY CREATIVE SPACE) - Bramasta, I Ketut Bayu Raditya; Purnawan, Ni Luh Ramaswati; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2023)
community, every member could understand the point and purpose of each other in order to achieve a goal. The purpose of this study is to describe the communication pattern of Dance Cover K-Pop The Key Creative Space Community in building self confidence among its members. This study conducted a descriptive qualitative method which the informant chose by purposive sampling technique. The data were gathered from interviews and documentation study. The result of this study is The Key Creative Space utilized two communication patterns namely, wheel communication which was used in a serious meeting or event, and the communication pattern in every channel which was used in relaxed meetings could enhance the self confidence of The Key Creative Space Dance Cover community which was initiated by the leader, Cryst. In this process Cryst is the leader always giving motivation and recommendation towards the members in order to fulfill the self-confidence of each member. Good communication made The Key Creative Space still exist until today.    Keywords : Communication Pattern, K-Pop Dance Cover Community, Self-confident .